Development of E-Booklet Learning Media to Improve Student Learning Outcomes on Parabolic Kinematics Materials - Sitorus, Oktavia; Putri, Desy Hanisa; Hamdani, Dedy (Asian Journal of Science Education, 2025)
This study aims to describe the feasibility of e-booklet learning media to improve student learning outcomes on parabolic kinematics material, describe the improvement of student learning outcomes after using e-booklet learning media on parabolic kinematics material, and describe students' responses to the e-booklet learning media that has been developed on parabolic kinematics materials. The method used is RD, using the ADDIE model. The results of the study showed: (1). Validation of media feasibility obtained a score with a percentage of 87.26%; (2) N-gain obtained a value of 0.77; (3) the assessment of student responses to the media, the benefit aspect, in total obtained a percentage of 89.14%. Based on the results, it can be concluded that the use of e-booklet learning media is very feasible to be used for parabolic kinematics material, to improve student learning outcomes, and received a very good response from students.